1995
DOI: 10.1111/j.1365-2125.1995.tb04468.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of acute and subchronic effects of dothiepin, fluoxetine and placebo on psychomotor and actual driving performance.

Abstract: 1 The acute and subchronic effects of dothiepin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
107
4
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(118 citation statements)
references
References 18 publications
6
107
4
1
Order By: Relevance
“…In humans, SSRIs such as paroxetine, fluoxetine and sertraline have been shown to induce significant increases in pupil diameter (Deijen et al 1989;Ramaekers et al 1995;Saletu and Grünberger 1988). Pupil size determines the amount of retinal illumination (Hart 1992), and as is stated by the Ferry-Porter Law (Davson 1976), CFF is directly proportional to the logarithm of the light intensity.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In humans, SSRIs such as paroxetine, fluoxetine and sertraline have been shown to induce significant increases in pupil diameter (Deijen et al 1989;Ramaekers et al 1995;Saletu and Grünberger 1988). Pupil size determines the amount of retinal illumination (Hart 1992), and as is stated by the Ferry-Porter Law (Davson 1976), CFF is directly proportional to the logarithm of the light intensity.…”
Section: Introductionmentioning
confidence: 97%
“…However, in the case of SSRIs, CFF measurements may not be readily interpretable in terms of cognitive changes, because mydriatic (pupil dilatation) effects of SSRIs may have significantly modified the outcome of CFF measurements (Ramaekers et al 1995;Warrington et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely for attention, ATD has in some studies (Booij et al 2005;Schmitt et al 2000) although not in all Sobczak et al 2002) been reported to improve performance in the Stroop Color Word Test (Jensen and Rohwer 1966), a test that relies heavily on focused attention. In line, serotonergic stimulation with SSRIs reduces sustained attention (Ramaekers et al 1995;O'Hanlon et al 1998;Schmitt et al 2002). These pharmacological manipulations of the serotonergic system are generally unspecific and affect many of the subtypes of pre-and postsynaptic serotonin receptors as well as the serotonin transporter (SERT), although in vivo studies using [ 11 C]DASB binding after ATD have failed to find significant changes in SERT binding (Praschak-Rieder et al 2005;Milak et al 2005).…”
Section: Introductionmentioning
confidence: 98%
“…In a recent review, concerning the effect of SSRIs in healthy individuals, 18 randomized trials using 39 different neuropsychological tests to investigate cognitive function were identified . Treatment with a SSRI was found to improve [Murphy et al 2008;Loubinoux et al 2005;Harmer et al 2004;Schmitt et al 2001;Knutson et al 1998Knutson et al , 1997, deteriorate [Riedel et al 2005;Schmitt et al 2002aSchmitt et al , 2001Fairweather et al 1997;Ramaekers et al 1995;Robbe and O'Hanlon, 1995] or have no effect on cognitive function [Peran et al 2008;Paul et al 2007Paul et al , 2002; Wingen et al 2006Wingen et al , 2005Loubinoux et al 2005;Riedel et al 2005;Siepmann et al 2003;Schmitt et al 2002aSchmitt et al , 2002bSchmitt et al , 2001Wilson et al 2002;Allen et al 1988;Fairweather et al 1997;Ramaekers et al 1995;Robbe and O'Hanlon, 1995]. It was concluded that the diverging findings could be a result of a number of methodological drawbacks.…”
Section: Introductionmentioning
confidence: 99%